Influencing E-commerce Performance in European Transition Economies: An Urgent Call for Digital Marketing - Kalemaj Eleni (Business Systems Research, 2025)
This study investigates the influence of digital marketing techniques on e-commerce businesses’ performance in Albania’s transition economy.